ICT-based system to predict and prevent falls (iStoppFalls): results from an international multicenter randomized controlled trial. Issue 1 (December 2015) - Gschwind, Yves; Eichberg, Sabine; Ejupi, Andreas; de Rosario, Helios; Kroll, Michael; Marston, Hannah; Drobics, Mario; Annegarn, Janneke; Wieching, Rainer; Lord, Stephen; Aal, Konstantin; Vaziri, Daryoush; et al.
Abstract Background Falls and fall-related injuries are a serious public health issue. Exercise programs can effectively reduce fall risk in older people. The iStoppFalls project developed an Information and Communication Technology-based system to deliver an unsupervised exercise program in older people's homes. The primary aims of the iStoppFalls randomized controlled trial were to assess the feasibility (exercise adherence, acceptability and safety) of the intervention program and its effectiveness on common fall risk factors. Methods A total of 153 community-dwelling people aged 65+ years took part in this international, multicentre, randomized controlled trial. Intervention group participants conducted the exercise program for 16 weeks, with a recommended duration of 120 min/week for balance exergames and 60 min/week for strength exercises. All intervention and control participants received educational material including advice on a healthy lifestyle and fall prevention. Assessments included physical and cognitive tests, and questionnaires for health, fear of falling, number of falls, quality of life and psychosocial outcomes. Results The median total exercise duration was 11.7 h (IQR = 22.0) over the 16-week intervention period. There were no adverse events. Physiological fall risk (Physiological Profile Assessment, PPA) reduced significantly more in the intervention group compared to the control group (F1, 127  = 4.54, p  = 0.035). There was a significant three-way interaction for fall risk assessed by the PPA between the high-adherence (>90 min/week;n  = 18, 25.4 %), low-adherence (<90 min/week;n  = 53, 74.6 %) and control group (F2, 125  = 3.12, n  = 75, p  = 0.044). Post hoc analysis revealed a significantly larger effect in favour of the high-adherence group compared to the control group for fall risk (p  = 0.031), postural sway (p  = 0.046), stepping reaction time (p  = 0.041), executive functioning (p  = 0.044), and quality of life (p for trend = 0.052). Conclusions The iStoppFalls exercise program reduced physiological fall risk in the study sample. Additional subgroup analyses revealed that intervention participants with better adherence also improved in postural sway, stepping reaction, and executive function. Trial registration Australian New Zealand Clinical Trials Registry Trial ID:ACTRN12614000096651 International Standard Randomised Controlled Trial Number:ISRCTN15932647